ANALISIS PENGARUH FAKTOR FUNDAMENTAL DAN EKONOMI TERHADAP RETURN SAHAM PADA PERUSAHAAN LQ 45 PERIODE 2010–2014 - Revicristia Ensev (Parsimonia - Jurnal Ekonomi dan Bisnis, 2015)
This research aims to test on how the effects of fundamental and economic factors on the return of company share including in LQ 45 for the period of 2010-2014. The fundamental factor is proxied with ratios of ROA, NPM, DER, DAR, EPS, PBV, CR, QR, TATO and ITO. The economic factor is proxied by the SBI interest rate level and inflation on the share return. The research samples consist of 16 companies including in LQ 45 for the period of 2010-2014. The sample collection method was using purposive sampling. The fundamental factor data in this research was obtained from Indonesia Capital Market Directory (ICMD). The economic factor data was obtained from Bank Indonesia sites. The factor selection used PCA test. The analysis technique used in this research was multiple linier regression to obtain the overall description on the correlation of one variable and other variables. The independent variables used after the PCA test are DAR, DER, QR, CR, ITO, SBI and inflation. The findings showed that the fundamental and economic factors have no effects on share return. From the findings, it is known that the independent variables can describe the share return namely only 3.1% and the remaining is described by other variables beyond the research. This shows that the share return is affected by other determinant beyond the independent variables used in this research.